Perjanjian Lisensi dan Royalti Sebagai Wujud Pelindungan Hak Cipta Dalam Waralaba Film - Hadianida, Nayla Sellyta; Safiranita, Tasya; Permata, Rika Ratna (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Copyright as one of the IP regimes can be utilized in the franchise business. Currently, the franchise business can also be applied to the entertainment industry, namely the existence of a movie franchise, which contains copyright. Although, the movie franchise is widely known by the public, but in practice there are still many who unaware the legal protection of movie copyright holders (franchisor) who give permission to the copyright recipient (franchisee) to franchise the movie. Therefore, the authors are interested in conduct research and further discuss the legal protection of copyright holders of movies whose creation is developed in the form of movie franchises. This research uses a normative juridical approach method with analytical descriptive research specifications and data analysis methods in this study were carried out using qualitative juridical methods. Based on the results of the discussion it is known that one of the implementation or embodiment of copyright protection for the copyright holders of the movie (franchisor) is the existence of a license agreement. The license agreement becomes the basis of the relationship between the franchisor and franchisee, which then from this agreement also arise the rights and obligations of the parties, one of which is royalty. The granting of royalty to the copyright holder of the movie becomes a form of appreciation and appreciation for the work created from the results of the mind of the copyright holder of the movie.